Sunday

December 21, 2014

December 21, 2014

Posted by **Anonymous** on Wednesday, January 28, 2009 at 3:49pm.

f(x) = e^(x^(-1))

f'(x) = -1(e^(x^(-2))e^(x^(-1))

f'(x) = -e^(x^(-2))e^(x^(-1))

?????

and... f(x) = 3^x

f'(x) = 3^x

- Math - Derivatives -
**Damon**, Wednesday, January 28, 2009 at 4:22pmd/dx e^u = e^u du/dx

here u = x^-1

du/dx = -1 x^-2

so

d/dx e^(x^-1) = -x^-2 e^(x^-1)

= -(1/x^2)e^(1/x^2)

Try the others using that recipe:

d/dx e^u = e^u du/dx

- Math - Derivatives -
**Anonymous**, Wednesday, January 28, 2009 at 4:34pmWOW that actually helps a lot and less confusing to solve! Thanks so much!

**Answer this Question**

**Related Questions**

Calculus - What is wrong with the following reasoning??? f(x) = 2^x f'(x) = x[2...

math - I studied derivatives before, but kind of forgot them all, is there a ...

Algebra - How do you simplify the following and please show all work. (-3x(-4 ...

Math(Please help) - Evaluate: f(x,y)=2x^3e^y a) partial derivative with respect ...

Calculus - derivatives - Okay, I want to find the derivative of (x^x)^(x^x)... ...

Property of logarithms - Using property of logarithms, how do I prove derivative...

Calculus--> bobpursley - How do you get m=0? from taking the second ...

calculus - derivatives differentiate y=x^7/3 So far I have Y=7/3X Is this all ...

Calculus - If x = t^2 + 1 and y = t^3, then d^2y/dx^2 = I know I can solve for t...

Algebra I - If i have two base variables with exponents for example: 4x(3x) ...